2010
DOI: 10.1094/phyto-100-2-0127
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Host Resistance by Independent Evolutionary Lineages of Beet necrotic yellow vein virus Involves a Parallel C/U Mutation in Its p25 Gene

Abstract: Breakdown of sugar beet Rz1-mediated resistance against Beet necrotic yellow vein virus (BNYVV) infection was previously found, by reverse genetics, to be caused by a single mutation in its p25 gene. The possibility of alternative breaking mutations, however, has not been discarded. To explore the natural diversity of BNYVV in the field and its effects on overcoming Rz1, wild-type (WT) and resistance-breaking (RB) p25 genes from diverse production regions of North America were characterized. The relative titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Hawaii and Australia, and TSWV SNI isolates, suggesting that Sw-5 resistance breakdown has occurred independently at least three times by convergent evolution. This is not unique, as breakdown of host resistance by independent evolutionary lineages have also been reported for Beet necrotic yellow vein virus (Acosta-Leal et al, 2010). Clade 2 included TSWV SRB isolates from Spain that had the T120N substitution and showed very low genetic divergence, suggesting a unique resistance-breakdown event.…”
supporting
confidence: 51%
“…Hawaii and Australia, and TSWV SNI isolates, suggesting that Sw-5 resistance breakdown has occurred independently at least three times by convergent evolution. This is not unique, as breakdown of host resistance by independent evolutionary lineages have also been reported for Beet necrotic yellow vein virus (Acosta-Leal et al, 2010). Clade 2 included TSWV SRB isolates from Spain that had the T120N substitution and showed very low genetic divergence, suggesting a unique resistance-breakdown event.…”
supporting
confidence: 51%
“…As three different single point mutations (corresponding to amino-acid modifications S/G 101, and to D/G 119 or D/A 119 ) were identified in the VPg viral cistron as candidates, different mutational pathways appeared to be available for SON41 to acquire virulence on va 2 background. Such an alternative adaptation process has been described for the acquisition of virulence for other plant viruses such as Rice yellow mottle sobemovirus and Beet necrotic yellow vein furovirus in the presence of Rymv1-2 (in rice genotypes) and Rz1 (in beet genotypes) resistance genes, respectively (Pinel-Galzi et al 2007;Acosta-Leal et al 2010). The central part of the VPg has already been associated to a va resistance breaking phenotype for Tobacco vein mottling potyvirus (Nicolas et al 1997) and PVY (Masuta et al 1999), but amino acids substitutions observed under our experimental conditions did not correspond to those previously proposed (i.e.…”
Section: Q E R F E V R R K M V E D D E I E T Q a L S H T S I Hmentioning
confidence: 99%
“…However, both the efficiency and the durability of resistance genes in cultivars will be affected by the extent to which a pathogen can adapt to become virulent to a gene (Harrison 2002). Virulence is intrinsic characteristics of the pathogen (Garcia-Arenal and McDonald 2003) and often results from single point mutations in the pathogen (Ayme et al 2007;HovmØller and Justesen 2007;Fudal et al 2009;Acosta-Leal et al 2010). RNA viruses are obligate parasites that exploit the host cellular metabolism to complete their infection cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of BNYVV A type strains, with four RNA components, to propagate to higher virus titres in Rz1 plants is associated with a specific composition of the P25 tetrad. All strains described in the past possess A67V exchange in P25 Acosta-Leal et al, 2010a) and Koenig et al (2009) showed by means of reverse genetics that this amino acid exchange alone is responsible for the induction of Rz1 resistance-breaking (RB) ability in an European A type strain. Bornemann & Varrelmann (2011) showed that RB strains retained their resistance-breaking abilities even after loading of another virus-free soilborne vector population.…”
Section: Introductionmentioning
confidence: 99%